JUSTICE, IMPARTIALITY, AND EQUALITY IN THE ALLOCATION OF SCARCE VACCINES: A REPLY TO SAUNDERS - Mclachlan, Hugh (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2022)
This paper is a reply to Saunders’s criticism of my previously published nonconsequentialist policy proposal regarding the use of a lottery for the distribution of scarce vaccine by the state in the face of an influenza pandemic. I argued there that, on the grounds of justice, the state should distribute some of the scarce vaccine it might hold to some of its healthcare employees and the rest to citizens randomly and equally on the principle of a lottery. Central to Saunders’s criticism is the claim that I mistakenly failed to take into account morally relevant differences in need and productive capacity between potential recipients of the vaccine. Central to my response here is that whether or not need and productive capacity are morally relevant factors depends on who or what is distributing the vaccine, to whom they are distributing it, and why they are doing so. For instance, discrimination between people in the distribution of publicly owned vaccine that is distributed as a prophylactic on the basis of their age is unjust whether or not it might be morally justifiable on other grounds.